Utilizing novel Aspergillus species for bio-flocculation: A cost-effective approach to harvest Scenedesmus microalgae for biofuel production - Tripathi G.; Pandey V.K.; Ahmad S.; Irum; Khujamshukurov N.A.; Farooqui A.; Mishra V. (My University, 2025)
The present study aimed to isolate a bioflocculating fungal strain from wastewater collected from a local bike garage. The isolate showed maximum similarity to Aspergillus species. The fungus was identified as Aspergillus flavus species F_GTAF1 IU (accession no OP703382). The isolated fungus was evaluated in terms of biomass recovery efficiency in Scenedesmus Sp. GTAF01. The extent of algal fungal co-pelletization was evaluated as a function of the algae-to-fungi ratio, volume of fungal culture in broth, agitation rate, and pH. results showed that at fungal culture volume of 60░%v/v, fungal culture volume of 1:3░%w/w, 100 rpm, and pH 3, 93.6░% biomass was obtained during the initial 5 h. At wavenumbers 1384 and 1024 cm-1 a significant alteration in the transmission percentage was observed in co-pellet compared to algae and fungal cells. This shows the significant role of C-H–H and C-N stretches in co-pellet formation. This study provides deep insight into effective microalgal harvesting along with the simultaneous extraction of lipids that can be used for the sustainable production of biodiesel. © 2024 The Authors